2021
DOI: 10.3389/fpls.2021.638452
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Nodulation Response to Cropping Interval and Inoculation in European Cropping Systems

Abstract: To support the adaption of soybean [Glycine max (L) Merrill] cultivation across Central Europe, the availability of compatible soybean nodulating Bradyrhizobia (SNB) is essential. Little is known about the symbiotic potential of indigenous SNB in Central Europe and the interaction with an SNB inoculum from commercial products. The objective of this study was to quantify the capacity of indigenous and inoculated SNB strains on the symbiotic performance of soybean in a pot experiment, using soils with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
(70 reference statements)
3
8
0
2
Order By: Relevance
“…The present study confirms the importance of inoculation for enhanced soybean yield in Europe ( Albareda et al, 2009 ; Zimmer et al, 2016 ; Halwani et al, 2021 ). Altogether, inoculation with our isolates significantly increased the protein content, grain yield, TGW, and pod number up to an average of 24, 32, 17, and 31%, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study confirms the importance of inoculation for enhanced soybean yield in Europe ( Albareda et al, 2009 ; Zimmer et al, 2016 ; Halwani et al, 2021 ). Altogether, inoculation with our isolates significantly increased the protein content, grain yield, TGW, and pod number up to an average of 24, 32, 17, and 31%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…We observed 2–4 times more nodules in both greenhouse experiments compared with the field trial, which corresponded with over three times higher soybean shoot N uptake. Nodule numbers in both greenhouse experiments were within the range of values reported for sites with a soybean-growing history in Muncheberg and Fehrow, Northeast Germany ( Halwani et al, 2021 ) and Central Germany ( Zimmer et al, 2016 ). These values are, however, lower than those in a report that used metadata involving numerous field trials in several countries and climates ( Thilakarathna and Raizada, 2017 ), re-echoing low soybean-rhizobium symbiosis in the Northeastern agro-climatic environment of Germany.…”
Section: Discussionsupporting
confidence: 73%
“…В 2021 году культуру ризобактерий в почву не вносили, а сев сои на площади 50 м 2 при междурядье 50 см (плотность ценоза 18 растений на квадратный метр) провели необработанными семенами перспективной формы сои А2, выявленной на полях Института генетики, физиологии и защиты растений в опытах 2018-2019 гг. Сев сои в 2021 г. провели необработанными семенами с учетом стимуляции клубенькообразования предысторией выращивания сои на опытном участке [5]. Для описания этапов органогенеза сои использовали общепринятую классификацию [6].…”
Section: материалы и методыunclassified
“…Предыстория участка, где в 2020 году в почву вносили культуру ризобактерий, позволяла ожидать хорошего клубенькообразования на корнях даже при севе необработанными семенами [5]. Первоначальные опыты, с отмывкой корневой системы на большую глубину, на всю толщину пахотного горизонта (0-30 см), показали преимущественную локализацию клубеньков в поверхностном слое чернозема, не глубже 10 см (Фиг.…”
Section: результаты и обсуждениеunclassified
“…Merr.) is one of the most important legume crops in numerous countries globally and is widely produced as a source of oil and protein [40,41]. Several studies observed improved biomass, nutrient acquisition, and soybean yield after biochar amendments [42,43].…”
Section: Introductionmentioning
confidence: 99%